Bochdalek Hernia and Intrathoracic Ectopic Kidney: Presentation of Two Case Reports and Review of the Literature - Sarac, M.; Bakal, U.; Tartar, T.; Canpolat, S.; Kara, A.; Kazez, A. (Wolters Kluwer Medknow Publications, 2018)
Bochdalek hernia is a congenital abnormality with high morbidity and mortality characterized by passage of the abdominal organs into the thoracic cavity through a diaphragmatic defect. Intrathoracic location of abdominal organs such as kidneys is very rare, with a reported incidence of only 0.25% in the literature. Herein, we present two cases of Bochdalek hernia with a herniation of intra-abdominal organ such as kidney that was treated in our clinic and compare this rare case with those in the literature. In both cases, the functionally normal kidneys were left in situ during diaphragmatic repair. No complications were observed during the postoperative period, and 10- and 1-year follow-ups. In cases with Bochdalek hernia associated with an intrathoracic ectopic kidney, the functionally normal ectopic kidneys were left in situ during repair of the diaphragmatic defect without complications.
Keywords: Bochdalek hernia; intrathoracic ectopic kidney; review of literature; two case reports